Importance of Voting at the Municipal Level: The Seniors’ Voices - Vallette, Salomé (Frontiers in Political Science, 2021)
While municipal elections in Quebec are characterized by low voter turnout, it appears that people over 65 years old are the ones who vote in higher numbers. In fact, this is the case for both federal and provincial elections. However, the lack of individual data on municipal elections does not yet allow us to say that seniors vote more than younger people. This finding invites political scientists to look at the electoral behaviour of individual voters and the importance attached to the act of voting at this level of government. In addition, the majority of studies on elections focus on the behaviours of voters living in large cities such as Montreal or Quebec City. In Quebec, the few studies that have looked at medium size municipality voting behaviour have mainly studied the cities of Quebec City, but not Montreal. Based on 19 interviews conducted with people aged between 65 and 84 and living in one medium size cities, Saint-Jean-sur-Richelieu, our research illustrates the importance of the exercise of a duty, the access to political information, the proximity of electoral behaviour and the influential role of seniors. According to participants, it is easier to talk to municipal candidates and get to know the person who will become their official representative, compared to the provincial and federal levels where it is more difficult to talk to candidates. Also, their knowledge of the municipal political system is better than when they were younger. While voting is similarly important at each level of government, participants felt that voting at the municipal level is directly relevant to them because of the municipal services but also by the influence they can have on their councillor.